El estudiante de Salamanca Related to the Aesthetics of Failure: an Approach from the Myth of Tantalus - Andrés Álvarez Touriño (Castilla: Estudios de Literatura, 2012)
This article is aimed to study the failure which has been considered to be the germ origin of the aesthetics in El estudiante de Salamanca. It deals with the fatal origin which sets the poem in relation to the pessimism of its own historical time, and which, in this survey, has been mainly regarded as the trace of the man´s anguish. Because of these reasons, this article shows the similarities of the poem with one of the greatest fatalistic myths: the Myth of Tantalus. His torments have been interpreted here as the metaphor of the man´s vital failure. This piece of work shares common keys with El estudiante de Salamanca, which reveal the essential nature of this internal conflict which concerns both characters: anxiety and fatalism threaten the poet.